Numerical analysis of wood air gasification in a bubbling fluidized gasifier with reactive charcoal as bed material. (April 2022) - Wan, Zhanghao; Yang, Shiliang; Hu, Jianhang; Bao, Guirong; Wang, Hua
Abstract: In this work, a reactive multiphase particle-in-cell model based on the Eulerian-Lagrangian framework is developed to numerically investigate the wood gasification process in a three-dimensional air-blown bubbling fluidized bed gasifier with the reactive charcoal as bed material. After the model validation, the impacts of gas velocity and initial bed height on the physical and thermophysical properties of gas-solid reacting flow are studied. The results show that lighter particles suspend at the upper part of the dense region with a larger rising velocity due to the density- and size-induced segregation. The vertical dispersion of both particle species is two orders of magnitude larger than the horizontal one. Large heat transfer coefficient (HTC) of solid phase appears in the rising path of biomass. Superficial gas velocity significantly affects the composition and the thermal properties of gas species. Heavy charcoal particles mainly distribute in the dense region with a high temperature and small HTC. Enlarging the superficial gas velocity increases the CO2 concentration whereas decreases the yields of combustible gas species. Initial bed height exerts an insignificant effect on the thermal property of gas phase, especially in the dense region.